Vegetation Dynamics and Ecological Potential of the Kehati Forest at UIN Malang: A Study of Carbon Stock, Hydrology, and Bird Diversity - Fitri Hariyanto; Muhammad Asmuni Hasyim; Narjun Najich; Nabila Zahra Azizah; Erlangga Bayu Permana; Muhammad Jabbar Dzikrullah (El-Hayah:Jurnal Biologi, 2026)
This research is a descriptive-quantitative study that evaluates the ecological condition of the Kehati Campus Forest at UIN Maulana Malik Ibrahim Malang through an integrated monitoring approach. The analysis includes estimating vegetation carbon stock, mapping tree distribution using geotagging methods, assessing groundwater infiltration potential, and identifying bird diversity as an ecosystem bioindicator. Vegetation data were collected by measuring tree diameter and height to calculate biomass and carbon storage, while geotagging was employed for spatial mapping of vegetation distribution. Groundwater infiltration potential was projected based on species dominance, whereas bird diversity was assessed using the line transect method. The results indicate that Artocarpus heterophyllus exhibited the highest dominance value and contributed substantially to carbon storage, with a total vegetation carbon stock of 2,341.78 kg. Geotagging successfully visualized stand distribution from seedling to mature tree stages, reflecting the dynamics of natural regeneration. The groundwater infiltration potential was also found to be relatively high, confirming the area’s role as a recharge zone. In addition, twelve bird species were recorded, with a Shannon-Wiener diversity index (H’ = 2.36), categorized as moderate. These findings underscore the strategic role of the Kehati Campus Forest as a conservation space, carbon sink, water regulator, and biodiversity habitat within the university environment.